COVID-19 knowledge-based system for diagnosis in Iraq using IoT environment - Bashar M. Nema; Yasmin Makki Mohialden; Nadia Mahmood Hussien; Nael Ali Hussein (Institute of Advanced Engineering and Science, 2021)
The importance and benefits of healthcare mobile applications is increasing rapidly, especially when such applications are connected to the internet of things (IoT). This paper describes a smart knowledge-based system (KBS) that helps patients showing symptoms of Influenza verify being infected with Coronavirus, commonly known as COVID-19. In addition to the systems’ diagnostic functionality, it helps these patients get medical assistance fast by notifying medical authorities using the IoT. This system displays patient’s location, phone number, date and time of examination. During the applications’ development, the developers used Twilio, short message service (SMS), WhatsApp, and Google map applications.